2014
DOI: 10.1016/j.cell.2014.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Clonal Dissection of Murine Small Cell Lung Carcinoma Progression by Genome Sequencing

Abstract: Summary Small cell lung carcinoma (SCLC) is a highly lethal, smoking-associated cancer with few known targetable genetic alterations. Using genome sequencing, we characterized the somatic evolution of a genetically engineered mouse model (GEMM) of SCLC initiated by loss of Trp53 and Rb1. We identified alterations in DNA copy number and complex genomic rearrangements and demonstrated a low somatic point mutation frequency in the absence of tobacco mutagens. Alterations targeting the tumor suppressor Pten occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
266
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(278 citation statements)
references
References 72 publications
7
266
0
Order By: Relevance
“…However, recent studies using lineage tracing, barcode sequencing, and whole-genome sequencing are shedding light on this question and have demonstrated a mostly polyclonal nature of metastasis (Fig. 5;McFadden et al 2014;Gundem et al 2015;Maddipati and Stanger 2015;Wagenblast et al 2015).…”
Section: Mic Heterogeneity: Clonal or Polyclonal Metastasismentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent studies using lineage tracing, barcode sequencing, and whole-genome sequencing are shedding light on this question and have demonstrated a mostly polyclonal nature of metastasis (Fig. 5;McFadden et al 2014;Gundem et al 2015;Maddipati and Stanger 2015;Wagenblast et al 2015).…”
Section: Mic Heterogeneity: Clonal or Polyclonal Metastasismentioning
confidence: 99%
“…Mutation analysis between the primary tumor and the metastatic lesions indicated polyclonal metastatic spread in the lymph nodes but not in the liver (McFadden et al 2014). Another whole-genome sequencing study analyzed 51 tumors of 10 prostate cancer patients, including primary tumors and multiple metastases in the same patients, and revealed the coexistence of multiple clones in the metastases, including those from metastasis-to-metastasis spreads (Gundem et al 2015).…”
Section: Mic Heterogeneity: Clonal or Polyclonal Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, multi-region comparisons have revealed extensive genomic variability across different geographic sectors of the tumor [33,34], or between the primary and metastatic tumors [35]. These studies, while using samples collected with a higher spatial or temporal resolution than those in TCGA and ICGC, often still contain heterogeneous populations of cells [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, the therapeutic strategy for SCLC has remained as platinum-based combination chemotherapy for the last several decades (4). Although a few recent SCLC sequencing studies have reported novel putative driver gene alterations, specific moleculartargeting therapy against such alteration is not yet available (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%